2014
DOI: 10.7314/apjcp.2014.15.6.2453
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Induces Apoptosis through Inhibition of the EpoR-Mediated JAK2/STAT5 Signalling Pathway in the TF-1/Epo Human Leukemia Cell Line

Abstract: Ginsenoside Rg1 is one effective anticancer and antioxidant constituent of total saponins of Panax ginseng (TSPG), which has been shown to have various pharmacological effects. Our previous study demonstrated that Rg1 had anti-tumor activity in K562 leukemia cells. The aim of this study was designed to investigate whether Rg1 could induce apoptosis in TF-1/Epo cells and further to explore the underlying molecular mechanisms. Here we found that Rg1 could inhibit TF-1/Epo cell proliferation and induce cell apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In terms of its positive effects, ginsenoside Rg1 reportedly has neurotropic and neuroprotective effects, counters oxidation and MPTP‐ or H 2 O 2 ‐induced apoptosis in neurons, stimulates differentiation and proliferation in human dental pulp cells and several mammalian cell lines, protects the cardiovascular system by decreasing oxidation and preventing apoptosis, and ameliorates diabetic cardiomyopathy by preventing ER stress‐induced apoptosis in diabetic rats . However, ginsenoside Rg1 has also been shown to inhibit cell proliferation and induce cell apoptosis, such as in the TF‐1/Epo human leukemia cell line . Although the latter finding suggests that ginsenoside Rg1 could be used to prevent and/or treat leukemia, the mechanisms through which ginsenoside Rg1 can inhibit/induce cell proliferation and apoptosis are unclear and warrant a detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of its positive effects, ginsenoside Rg1 reportedly has neurotropic and neuroprotective effects, counters oxidation and MPTP‐ or H 2 O 2 ‐induced apoptosis in neurons, stimulates differentiation and proliferation in human dental pulp cells and several mammalian cell lines, protects the cardiovascular system by decreasing oxidation and preventing apoptosis, and ameliorates diabetic cardiomyopathy by preventing ER stress‐induced apoptosis in diabetic rats . However, ginsenoside Rg1 has also been shown to inhibit cell proliferation and induce cell apoptosis, such as in the TF‐1/Epo human leukemia cell line . Although the latter finding suggests that ginsenoside Rg1 could be used to prevent and/or treat leukemia, the mechanisms through which ginsenoside Rg1 can inhibit/induce cell proliferation and apoptosis are unclear and warrant a detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that chemical or physical injury can affect the complex and precisely orchestrated process of normal embryonic development, causing malformation or miscarriage during preimplantation and postimplantation embryogenesis. Given the conflicting reports indicating that ginsenoside Rg1 may induce or prevent cell apoptosis, it is very important to examine whether this compound has potential teratogenic effects on embryonic development. In this study, we show that incubation of mouse blastocysts with ginsenoside Rg1 for 24 h induced apoptosis in blastocysts and decreased the number of ICM cells, but had no effect on TE cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 40 ginsenoside compounds have been identified [25]. Some of them, Rg1, Rg3, Rh1 and Rh2, for example, show the potent anticancer activity [24], [26][28]. Ginsenoside Rg3, a bioactive extracts of Panax ginseng , has various medical effects, such as anti-tumor [29][32], anti-oxidant, anti-inflammation properties [33], [34], inhibiting scar hyperplasia of skin [35] and angiogenesis [36].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 (5 ng/ml) also significantly upregulated the expression of the mesenchymal marker vimentin, downregulated the expression of the epithelial marker E-cadherin and promoted invasion and migration of HepG2 cells. Previous studies have demonstrated that ginsenoside Rg1 may exert anti-cancer properties (13,18,26,27), however, this is the first study, to the best of our knowledge, to demonstrate that ginsenoside Rg1 may be a potential inhibitor of invasion and migration. The results of the transwell and wound-healing assays demonstrated that ginsenoside Rg1 inhibited TGF-β1-induced cell invasion and migration in HepG2 cells.…”
Section: Discussionmentioning
confidence: 61%